The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture, 1989)
Pages: 1 vol. (398 p.) ;
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Le Bordel: Milieu De Travail Contrôlé - Lévesque, Andrée (Labour / Le Travail, 1987)
PENDANT LONGTEMPS, des milliers de femmes gagnèrent leur vie dans des bordels à Montréal. L'étude de leur milieu de travail pendant les années vingt et trente révèle une organisation hiérarchique et des conditions dont le contrôle échappait aux principales intéressées. L'appareil judiciaire et policier, les organisations de réformes sociales, le clergé et les médecins hygiénistes affectaient, par la tolérance ou la répression, le cadre dans lequel s'exerçait la prostitution. Plus directement, les souteneurs, les tenancières et leurs gérantes déterminaient les conditions quotidiennes de travail. Les changements observés pendant toute cette période sont plus imputables à la vigilance policière qu'aux fluctuations économiques ou aux efforts des travailleuses elles-mêmes.
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; montréal; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; thématiques; travail; travail du sexe; travail du sexe-prostitution